Microstructural Bone Changes Are Associated With Broad-Spectrum Autoimmunity and Predict the Onset of Rheumatoid Arthritis - Simon, David; Kleyer, Arnd; Bui, Cong Duy; Hueber, Axel; Bang, Holger; Ramming, Andreas; Rech, Jürgen; Schett, Georg (Arthritis and Rheumatology, 2022)
Objective To assess if microstructural bone lesions in individuals at risk of developing rheumatoid arthritis (RA) are related to the spectrum of anti-modified protein antibodies (AMPAs) and affect the risk of developing RA. Methods Cortical microchannels as well as cortical and trabecular bone mineral density (BMD) volumes (expressed as mg hydroxyapatite/cm(3)) were analyzed by high-resolution peripheral quantitative computed tomography of the hand joints of individuals at risk of RA. AMPA response was profiled, including reactivities against citrullinated proteins (vimentin, enolase, and fibrinogen) as well as carbamylated and acetylated vimentin. All subjects were followed up for the development of RA. Results Subjects at risk of developing RA (n = 75) who had broad-spectrum AMPAs (6-8 reactivities) had significantly more severe microstructural changes, including a higher mean +/- SD number of cortical microchannels per joint (95 +/- 3) and lower total volumetric BMD (vBMD; 265 +/- 45), trabecular vBMD (176 +/- 42), and cortical vBMD (585 +/- 138), than those with moderate AMPA reactivity (3-5 reactivities) (number of cortical microchannels, 79 +/- 30; total vBMD, 293 +/- 33; trabecular vBMD, 195 +/- 32; and cortical vBMD, 627 +/- 91) and those with narrow AMPA reactivity (1-2 reactivities) (number of cortical microchannels, 47 +/- 20; total vBMD, 311 +/- 34; trabecular vBMD, 211 +/- 30; and cortical vBMD, 674 +/- 56). Progressors to RA had significantly higher numbers of cortical microchannels (103 +/- 30 versus 71 +/- 35) and lower bone volume (258 +/- 37 versus 295 +/- 34) compared to nonprogressors. Furthermore, rate of progression to RA was high in subjects with broad AMPA reactivity (48%) versus those with medium AMPA reactivity (26%) or narrow AMPA reactivity (0%), as well as in those with a high number of cortical microchannels (44%) versus those with a low number of cortical microchannels (10%). Conclusion Microstructural changes in individuals at risk of RA are associated with broad-spectrum autoimmunity and predict the onset of RA. These data support the concept of structural priming of joints by autoimmunity before the onset of the inflammatory phase of the disease.
CRIS-Team WoS Importer:2022-02-11